Porous silicon based fuel cell type alcohol vapor sensor - Duzgun, Pinar; Nuhoglu, Cigdem; Yuksel, Sureyya Aydin (ELSEVIER SCIENCE SA, 2025)
In this study, fuel cell type alcohol vapor sensors based on Silver/Porous silicon/nSi Schottky diodes are presented for the first time in the literature. The structures produce fuel cell-like short circuit current with alcohol vapor at room temperature without requiring any external power source. The sensors were produced with PS layers with two different morphologies and their effects on alcohol vapor sensitivity were investigated. It was determined that the devices subjected to alcohol vapor tests using four different alcohols (methanol, ethanol, 2propanol and butanol) in the range of 50-350 ppm detected all alcohols with different short circuit current changes. Our sensors, which were determined to have the highest sensitivity to methanol with the lowest carbon chain, decrease their sensitivity depending on the carbon chain length. While the barrier height of the diodes for both PS structures decreases linearly with increasing methanol vapor concentration, a shift towards lower voltages occurred in the reverse bias breakdown voltages in the PS layered device with less sponge-like peak areas. When the morphological, optical and structural characterizations of the PS layers were examined together, it was seen that the morphological properties were decisive for the diode parameters at the initial conditions and that these parameters were affected by alcohol vapor at different levels and with similar relationships. The short circuit current created by the sensors in methanol vapor (50-350 ppm) at room temperature and atmospheric pressure, depending on the alcohol vapor concentration, varied between 1.00 and 150 nA.cm-2.
Keywords: Porous Silicon; Fuel Cell Type; Alcohol vapor; Sensor; SCHOTTKY DIODE STRUCTURES; GAS-SENSOR; RAMAN ANALYSIS; HYDROGEN; FABRICATION; ELECTROLESS; TEMPERATURE; POLYSILICON; EFFICIENT; MECHANISM; Engineering; Instruments & Instrumentation